Rights to free from corruption: A vernacular mobilization of anti-corruption movement in Indonesia - Miftachul Choir (Universitas Trunojoyo Madura, 2022)
This study examines how the non-governmental organizations (NGOs) in Indonesia built anti-corruption movements despite the constraining sociopolitical context in Indonesia. Applying collective action framework, this research argues that NGOs translate, transform, and circulate the meaning of anti-corruption activism set in the United Nations Convention against Corruption (UNCAC) into an appropriate environment. The translation results in rights consciousness through redefining the meaning of corruption, victimization of corruption, mainstreaming anti-corruption techniques, circling the human rights frame through capacity-building training, and multiplying the task of vernacularization to local NGOs. This research selected Indonesia Corruption Watch (ICW) as a case study, examined their article of association, annual report, program report, and their educational campaign. Interview conducted with participants of their educational program. The data analyzed using discourse analysis to see how ICW problematizes and prognose corruption, and identifying the key framing of their activity. The study contributes to the scholarship of Indonesian social movements that were paying more attention to the efficacy and evaluation of NGOs movement rather than the process of how they built the movement. This study also argues that in the absence of leftist politics, human rights discourse is applicable to articulate justice demands and mobilize citizens for liberal reforms.